A Study on Moment Capacity of Timber Beam with Passive Prestressing - Leng, Violet; Yeoh , David (Recent Trends in Civil Engineering and Built Environment, 2021)
In Malaysia, Kempas timber is widely used as structural components for civil construction. The application of prestressed timber starts emerging in Malaysia to enhance the load carrying capacity and allow the use of longer span with reduced cross-sectional size simultaneously, since timber is weak in bending and susceptible to cracking under flexural load. This research was conducted to investigate the change in bending strength and moment capacity of timber beam with passive prestressing rods installed at different lever arm positions, and the enhancement of moment capacity of timber beam with and without passive prestressing. Five Kempas timber specimen configurations with a volume of 40mm×90mm×900mm were prepared for four-point bending test, and their flexural behaviors were evaluated subsequently. Strengthening tension side of timber beam had the greatest enhancement of flexural strength and moment capacity among the specimens. In the absence of the torsion influence, all prestressing schemes had a significant improvement in timber properties compared to non-prestressed beam. In terms of timber stiffness, it has been improved in all prestressed sample configurations, with the exception of TBN specimens. Future research should increase number of specimens to minimize variation in timber properties.